Collaborative Learning Platform for Academicians in Libya - Noureddon Beleid; Kinn Bakon; Mitrran Menon (AlQalam Journal of Medical and Applied Sciences, 2024)
Higher education academicians face a variety of difficulties, such as the need for improved collaboration, streamlined communication, and effective resource management. In order to tackle these concerns, this study investigates the unique challenges that academicians in higher education face. The study emphasizes the need for integrated features and user interfaces that are simple to understand and customized for a particular requirement of higher education. Moreover, by exploring the recognition and understanding of these barriers, the study not only clarifies the complex terrain of difficulties but also establishes the foundation for the creation of a platform for collaborative learning. With a focus on the problems faced by academicians, this platform will include features like a forum that is easy to use, the ability to share resources, a powerful search engine, a section devoted to frequently asked questions, and a chatbot that can engage users. Together, these elements seek to offer a thorough resolution to the problems noted, promoting enhanced dialogue, information sharing, and instructional effectiveness among academicians. يواجه الأكاديميون في التعليم العالي مجموعة من الصعوبات، مثل الحاجة إلى تحسين التعاون، وسهولة الاتصالات، وإدارة االمصادرالموثوقة الفعّالة. ومن أجل معالجة هذه المخاوف، تبحث هذه الدراسة في التحديات التي يواجهها الأكاديميون في التعليم العالي. وتؤكد الدراسة على الحاجة إلى ميزات متكاملة وواجهات مستخدم تكون سهلة الفهم ومصممة خصيصًا لمتطلبات معينة للتعليم العالي. وعلاوة على ذلك، من خلال استكشاف التعرف على هذه العوائق وفهمها، فان هده الدراسة لا توضح الصعوبات المعقدة فحسب، بل تضع أيضًا الأساس لإنشاء منصة للتعلم التعاوني. مع التركيز على المشاكل التي يواجهها الأكاديميون، ستشمل هذه المنصة ميزات مثل منتدى سهل الاستخدام، والقدرة على مشاركة مصادر المعلومات، ومحرك بحث قوي، وقسم مخصص للأسئلة الشائعة، وبرنامج محادثة آلي يمكنه إشراك المستخدمين. وتسعى هذه العوامل معًا إلى تقديم حل شامل للمشاكل المذكورة، وتعزيز الحوار المعزز، وتبادل المعلومات، وفعالية التعلم والاستفادة بين الأكاديميين